PSVII-9 Agronomic characteristics and nutrient composition of purple prairie clover grown under irrigated and dryland conditions. (5th December 2019) - Wang, Yuxi; Iwaasa, Alan; Xu, Zhong-Jun; Acharya, Surya; McAllister, Tim
Abstract: Dry matter (DM) yield, nutrient composition, and in vitro digestibility of three populations (Common, AC Lamour, Bismarck) of purple prairie clover (PPC; Dalea purpurea Vent.) were determined in a 3-year study. Test plots of the populations were established in the 1st year under irrigation and dryland and whole plants were harvested at vegetative, full flower and late flower stages for determination of DM yield and nutritional characteristics in the 2nd and 3rd year. Only one cut per season was achieved for all populations under both growing conditions. The DM yield was similar among the three populations but irrigated land yielded higher (P < 0.01) DM than dryland in both years. The average DM yields (kg/ha; mean±SD) at the vegetative, full flower and late flower stages were 4739±1431, 4988±1547 and 6715±1580 under irrigation and 1423±479, 2014±348 and 2297±942 under dryland. Nutrient composition (organic matter, protein, neutral and acid detergent fibres and minerals) was similar among the three populations. Protein content was higher (P < 0.01) but neutral and acid detergent fibre content was lower (P < 0.05) in plants grown under irrigation than on dryland. Condensed tannin concentration was higher (P < 0.05) in plants grown under dryland than under irrigation. In vitro organic matter digestibility was higher (P < 0.05) for PPC grown under irrigation than on dryland. The PPC was readily established on both dry and irrigated land with comparable nutrient content to that of alfalfa and sainfoin under the similar growing conditions. Purple prairie clover has potential as an alternative legume forage, but its yearly yield is substantially lower than conventional legume forages.